2018
DOI: 10.1073/pnas.1708293115
|View full text |Cite
|
Sign up to set email alerts
|

Field study of charitable giving reveals that reciprocity decays over time

Abstract: SignificanceReciprocity motivates a wide range of cooperative behaviors (e.g., tipping, exchange of favors, customer loyalty, etc.). It is typically assumed that, after a reciprocal relationship is triggered, reciprocal motives remain stable over time. Using a large-scale field study, we show that this is not the case. Instead, we find that reciprocity decays rapidly over time. We analyze donation solicitations sent from a university hospital system to its patients and show that patients are less likely to don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…However, Mrkva (2017) found that time delay, compared to baseline, increases charitable donations, whereas Gärtner (2018) found that time pressure increases self-regarding decisions in the dictator game, but only when the dictator game is presented without a status-quo; by contrast, Gärtner (2018) found that time pressure has no effect on decisions when the statusquo is set on the self-regarding choice or on the altruistic choice. Chuan, Kessler and Milkman (2018) found that 30-day time delay between the provision of medical care and a donation solicitation decreases the likelihood of a donation by 30%. Grolleau, Sutan, El Harbi and Jedidi 2018 Fischbacher, Thöni and Utikal (2014) conducted a series of 20 mini dictator games with varying inequality but keeping the social efficiency constant (100 points for 10 games and 94 for 10 games).…”
Section: Review Of the Empirical Evidencementioning
confidence: 99%
“…However, Mrkva (2017) found that time delay, compared to baseline, increases charitable donations, whereas Gärtner (2018) found that time pressure increases self-regarding decisions in the dictator game, but only when the dictator game is presented without a status-quo; by contrast, Gärtner (2018) found that time pressure has no effect on decisions when the statusquo is set on the self-regarding choice or on the altruistic choice. Chuan, Kessler and Milkman (2018) found that 30-day time delay between the provision of medical care and a donation solicitation decreases the likelihood of a donation by 30%. Grolleau, Sutan, El Harbi and Jedidi 2018 Fischbacher, Thöni and Utikal (2014) conducted a series of 20 mini dictator games with varying inequality but keeping the social efficiency constant (100 points for 10 games and 94 for 10 games).…”
Section: Review Of the Empirical Evidencementioning
confidence: 99%
“…However, Mrkva (2017) found that time delay, compared to baseline, increases charitable donations, whereas Gärtner (2018) found that time pressure increases self-regarding decisions in the dictator game, but only when the dictator game is presented without a status-quo; in contrast, Gärtner (2018) found that time pressure has no effect on decisions when the status-quo is on the selfregarding choice or on the altruistic choice. Chuan, Kessler and Milkman (2018) found that 30-day time delay between the provision of medical care and a donation solicitation decreases the likelihood of a donation by 30%. Grolleau, Sutan, El Harbi and Jedidi (2018) found that time delay decreases dictator game giving in Tunisia.…”
Section: Review Of the Empirical Evidencementioning
confidence: 99%
“…First, because of our experiment was conducted using paper and pencils, it was extremely complicated and time‐consuming to provide feedback to subjects in the middle of the experiment. Second, we wanted to investigate whether giving behavior may decay over time as documented in other studies (e.g., Chuan, Kessler, & Milkman, ). Giving is often a spontaneous act of generosity, but as time progresses, an individual may rely less on the unconscious and fast‐thinking and rely more on sophisticated and analytical thinking.…”
Section: Experimental Designmentioning
confidence: 99%